Migrant Women’s Help-Seeking Decisions and Use of Support Resources for Intimate Partner Violence in China - Hu, Ran (Violence against women, 2022)
In China, women who domestically relocate from rural or less developed regions to major cities are at a higher risk for intimate partner violence (IPV) than their non-migrant counterparts. Few studies have focused on Chinese domestic migrant women’s help-seeking for IPV and their use of different sources of support. The present study aimed to identify factors that influence migrant women’s help-seeking decisions. In addition, we also examined factors that contribute to migrant women’s use of diverse sources of support for IPV. A sample of 280 migrant women victimized by IPV in the past year at the time of the survey was drawn from a larger cross-sectional study conducted in four major urban cities in China, including Beijing, Shanghai, Guangzhou, and Shenzhen. Using a multinomial logistic regression model and a zero-inflated Poisson model, we found that factors influencing migrant women’s help-seeking decisions and their use of diverse sources of support included socioeconomic factors, IPV type, relationship-related factors, knowledge of China’s first anti-Domestic Violence Law, and perception of the effectiveness of current policies. We discuss implications for future research and interventions.